Evaluation of Environmental Management at Pulang Pisau Regional General Hospital Based on Environmental Impact Assessment Studies and Regional Development - Tidja, Agustinus Richardo; Syafari, Muhammad Riduansyah; Shaddiq, Syahrial (International Journal of Multidisciplinary Approach Research and Science, 2025)
This study aims to evaluate environmental management at Pulang Pisau Regional General Hospital (RSUD) within the framework of participatory development planning. The research employs a qualitative approach with a descriptive method, collecting data through interviews, observations, and documentation. Data analysis follows the Miles and Huberman model, with validation through methodological and source triangulation. The findings indicate that environmental planning and management at RSUD Pulang Pisau remain technocratic, with limited public involvement. The lack of public dialogue spaces and multi-stakeholder consultations results in low community participation in sustainable development. Implementing medical and liquid waste management policies follows national regulations but still faces challenges in resource efficiency and environmental impact monitoring. This study recommends strengthening inclusive environmental governance by establishing multi-stakeholder forums and public consultation mechanisms and enhancing community education and empowerment in environmental monitoring. Policy evaluation based on George C. Edward III's implementation theory highlights the importance of clear communication, resource availability, stakeholder commitment, and an effective bureaucratic structure in successfully implementing environmental policies. This research emphasizes that active public participation in hospital environmental management is not merely a technical aspect but also an integral part of an inclusive and sustainable development process.